1954
DOI: 10.1073/pnas.40.11.1037
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Mutations in Drosophila by Tertiary -Butyl Hydroperoxide

Abstract: The mutagenic action of certain organic peroxides was first shown in work of Wyss, Stone, et al.1 in 1947-1948 on Micrococcus pyogenes (Staphylococcus aureus) and, soon afterward, in work of Dickey, Cleland, and Lotz2 in 1948 on Neurospora crassa. Because of the importance of peroxides in the production of mutations in microorganisms and as intermediates in the production of mutations by ultraviolet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1957
1957
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The only other hydroperoxide that has been reported to be mutagenic is tert-buty\. This compound is mutagenic in Drosophila (Altenburg, 1954) and in Neurospora (Dickey et al, 1949) and induces chromosome aberrations in Vicia faba (Loveless, 1951). Cumene hydroperoxide has been reported by Latarjet et al (1958) to be negative in a transformation test.…”
Section: Discussionmentioning
confidence: 93%
“…The only other hydroperoxide that has been reported to be mutagenic is tert-buty\. This compound is mutagenic in Drosophila (Altenburg, 1954) and in Neurospora (Dickey et al, 1949) and induces chromosome aberrations in Vicia faba (Loveless, 1951). Cumene hydroperoxide has been reported by Latarjet et al (1958) to be negative in a transformation test.…”
Section: Discussionmentioning
confidence: 93%
“…The specific ozone reaction products which produced the mutagenic effects in the above studies have not been identified. In nonaquatic organisms, however, organic peroxides and hydroperoxides have been shown to be capable o f inducing lethal mutations in Drosophila (Altenburg 1954, Sobels .1956), Neurospora (Dickey et al 1949), and Escherichia coli (Davis 1959). The LDS0 of linoleic acid peroxide (0.26 vrnol/g) was comparable to the level of organic peroxide previously found in mice after receiving an LD50 dose of X-rays (0.22 vmol/g) (Horgan et a1 .…”
Section: Controlsmentioning
confidence: 99%